Theoretical Predictions of Ge14BixSe76-xIn10 Chalcogenide Glasses - Gupta, Shilpa; Saxena, Manish (IJRDO-Journal of Applied Science, 2016)
Chalcogenide glasses have attracted much attention in recent past as physical properties of chalcogenide glasses make them ideal for incorporation into lasers and other active devices. In the present work, the effect on the physical properties of Ge14BixSe76-xIn10 (x = 2, 4, 6, 8, 10 at. %) chalcogenide glasses with the variation in bismuth content has been studied theoretically. All the parameters, studied here, have been found to vary linearly with change in Bi concentration which indicates this system suitable for phase change optical recording and find applications in rewritable optical recording.